Use of complementary/alternative therapies by women with advanced-stage breast cancer - Glaspy John; Wenger Neil; Albert Paul S; Andersen Ronald; Shen Joannie; Cole Melissa; Shekelle Paul (BMC, 2002)
Abstract Background This study sought to describe the pattern of complementary/alternative medicine (CAM) use among a group of patients with advanced breast cancer, to examine the main reasons for their CAM use, to identify patient's information sources and their communication pattern with their physicians. Methods Face-to-face structured interviews of patients with advanced-stage breast cancer at a comprehensive oncology center. Results Seventy three percent of patients used CAM; relaxation/meditative techniques and herbal medicine were the most common. The most commonly cited primary reason for CAM use was to boost the immune system, the second, to treat cancer; however these reasons varied depending on specific CAM therapy. Friends or family members and mass media were common primary information source's about CAM. Conclusions A high proportion of advanced-stage breast cancer patients used CAM. Discussion with doctors was high for ingested products. Mass media was a prominent source of patient information. Credible sources of CAM information for patients and physicians are needed.